Implementation of the Balanced Score Card to Achieve Strategic Goals in the State Islamic Religious Colleges - Hadijaya, Yusuf; Nasution, Inom; Suhairi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
Performance Management in State Islamic Religious Colleges (PTKIN) Indonesia are still often ignoring the identification of stakeholders and the primary performance indicator of management measurement goals. The Balanced Score Card (BSC) as a management approach translates the direction of Higher Education developing into an action based on the initiatives identity number and management measurement goal systems. The context aims to determine the implementation of the Balanced Score Card at PTKIN with four perspectives which are connected as part of the chain driving to achieve the strategic point of Higher Education and performance of higher education results model. This research is qualitative research with the technique of data collection on observation, in-depth interviews, and documentation. The results paper shows that the Balanced Score Card is the performance integrating on the management system at UIN Jakarta, UIN Yogyakarta, and UIN North Sumatera through the making of Score Cards with the processing of strategy maps to achieve its strategic point of higher education objectives. The Map Strategy is preparing as a companion model for its BSC implementation management goal of Higher Education.